Integrated Management Information System Training in the Professional Development of Learning and Instruction of Academic Staff - Melliana; Deisye Supit; Apriyanto; Okki Navarone Wibisono (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
The limited implementation of Integrated Management Information Systems (IMIS) in higher education is reflected in low faculty participation, recurring data errors, and delays in academic services. This study aims to evaluate the effectiveness of Continuing Professional Development (CPD) schemes in enhancing IMIS adoption, improving service efficiency, and increasing data accuracy. A quantitative approach was employed using a survey design involving 340 academic staff selected through proportional stratified random sampling. Data were collected using a Likert scale questionnaire and analyzed using descriptive statistics, multiple linear regression, independent t-test, and ANOVA. The findings reveal that post training mentoring has the most significant impact on IMIS adoption, service speed, and data accuracy, while active participation in CPD also improves motivation, digital skills, and self-confidence among academic staff. Additionally, disparities in system adoption across institutional units were identified, influenced by differences in digital readiness and institutional support. It can be concluded that successful digital transformation in higher education depends not only on system availability but also on the effectiveness of sustainable CPD strategies. The practical implications highlighting that the importance of integrating mentoring, blended learning, and communities of practice to enhance academic service quality and operational efficiency.